Enhanced impact strength of glyptal resin composites with red mud: A comparative study of incorporation methods - Melnyk, Liubov (Technologies and Engineering, 2025)
The purpose of this study was to investigate the use of red mud, as a sustainable filler for glyptic resin composites and injection methods on their impact strength, as well as to optimise the properties of the composites and promote environmentally friendly use of materials. Glyptal resin was synthesised from glycerol and phthalic anhydride. Two methods of red mud introduction were employed: mechanical mixing and in situ synthesis. The concentration of red mud ranged within 7-56 wt%. The impact strength of the resulting composites was evaluated using standard tests. The study showed that red mud significantly increases the impact strength of composites based on glyptal resins. The in situ synthesis method provided the best results, with a maximum impact strength of 22.05 N-m at a red mud content of 36 wt%, which is 12.5% greater than that of mechanically mixed composites. The optimum filler concentration was determined at 36 wt%, with a sharp decrease in strength at greater concentrations due to particle agglomeration. In addition, the impact strength increased with increasing synthesis time, reaching its peak at 480 min for composites with 7 wt% red mud. This study provided new insights into the integration of red mud as a reinforcing filler in glyptic resins and highlighted the advantages of in situ synthesis in achieving better dispersion and matrix interaction, which contributes to the development of stable polymer composites. The findings demonstrated the possibility of using red mud, a complex industrial waste, in the production of high-performance polymer composites. The study offered practical recommendations for optimising the concentration of fillers and synthesis methods, which would contribute to the development of environmentally friendly and cost-effective materials for industrial applications.